Organizational and Behavioral Factors Associated with Infection Prevention and Control Policy Implementation among Nurses: A Cross-Sectional Study in a District Hospital - Rahmat Alyakin Dakhi; Jasmen Manurung; Astrid Carmia Dachi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Healthcare-associated infections (HAIs) remain a critical indicator of healthcare quality and patient safety. HAIs contribute to increased morbidity, prolonged hospitalization, higher healthcare costs, and mortality. At Lukas Hilisimaetano Hospital, the incidence of HAIs exceeded the national minimum service standard of <1.5%, reaching 10.73% in 2023 and 7.31% in 2024. These findings suggest that the implementation of infection prevention and control (IPC) policies in the hospital has not been fully optimized. Based on Edward III’s policy implementation theory, policy implementation is influenced by communication, resources, disposition, and bureaucratic structure. This study aimed to analyze organizational and behavioral factors associated with IPC policy implementation among nurses. Methods: A cross-sectional analytical study was conducted from May to November 2025 at Lukas Hilisimaetano Hospital. All 45 nurses working in inpatient units were included using total sampling. Data were collected using structured questionnaires and observation sheets measuring communication, resources, disposition, bureaucratic structure, and IPC policy implementation. Instrument validity was assessed through expert review, and reliability testing showed acceptable internal consistency (Cronbach’s alpha >0.70). Data were analyzed using Chi-square and binary logistic regression. Results: Communication (OR=7.90; p=0.003), resources (OR=9.44; p=0.001), disposition (OR=14.40; p=0.001), and bureaucratic structure (OR=8.20; p=0.001) were significantly associated with IPC policy implementation in bivariate analysis. Multivariate analysis showed that disposition (AOR=8.26; 95% CI: 1.77–38.58; p=0.008) and resources (AOR=4.71; 95% CI: 1.13–19.58; p=0.033) remained significantly associated. The strong association between disposition and IPC implementation highlights the importance of behavioral commitment among nurses in supporting infection prevention practices. Conclusion: IPC policy implementation is associated with both organizational and behavioral factors, with disposition emerging as the strongest associated factor. Findings should be interpreted cautiously due to the cross-sectional design and small sample size. Strengthening behavioral commitment and ensuring adequate resources may support improved IPC implementation in similar settings.